An Educational Intervention to Promote Access to Rehabilitation for People Living with HIV. - Solomon, Patricia; Salbach, Nancy M.; O'Brien, Kelly K.; Nixon, Stephanie; Baxter, Larry; Gervais, Nicole (Disability, CBR & Inclusive Development)
This paper describes the design and novel features of an evidence- and theoryinformed client activation intervention to increase the capacity of people living with HIV to: 1) self-manage their health-related challenges using rehabilitation strategies, and 2) communicate their rehabilitation needs to their healthcare providers to improve access to rehabilitation. Building on social-cognitive theory and evidence, the intervention is a community-based workshop to develop knowledge and skills of people living with HIV to advocate for rehabilitation services. Novel features include engagement of community-based organisations in a train-the-trainer delivery model, a problem-based learning design to promote problem-solving and application, and a focus on client-centred practice. The intervention is flexible and adaptable. Health providers in other countries and contexts could use the pedagogical features to develop a workshop to meet their local needs. Given that most knowledge transfer interventions aim to change health provider behaviour, the focus on teaching people living with HIV to advocate for referral to rehabilitation is unique. The workshop model may be of interest to those in communities where access to rehabilitation for people living with HIV can be limited due to a lack of knowledge of the potential role of rehabilitation.